PENGEMBANGAN DAN UJI KELAYAKAN BOARD GAME EDUKATIF “SAKPOLE” SEBAGAI MEDIA PEMBELAJARAN BUDAYA PADA MATA PELAJARAN IPAS KELAS IV SD KEMALA BHAYANGKARI 02 SEMARANG - Prameswari, Shanti; Ayyub Hamdanu Budi Nurmana; Muhammad Sholikhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The sustainability of Indonesia's traditional games is increasingly challenged by the rapid expansion of digital entertainment among elementary-school-aged children, widening the gap in interactive learning media capable of recontextualizing local wisdom. This study develops and examines the feasibility of “Sakpole”, an educational board game as a cultural learning medium for the Natural and Social Sciences (IPAS) subject in Grade IV, with students of SD Kemala Bhayangkari 02 Semarang as subjects. Development followed the Multimedia Development Life Cycle (MDLC) of Luther–Sutopo. Feasibility was examined through alpha testing by a media expert and a subject-matter expert, followed by beta testing among students, using a five-point Likert-scale questionnaire; the visual elements were further interpreted through Peircean semiotics (icon, index, symbol) and Kress and van Leeuwen's visual grammar. The resulting product comprises a Nusantara-map game board, four endemic fauna characters dressed in regional traditional attire, three card categories, and a system of physically embedded traditional mini-games. Alpha testing produced feasibility scores of 88.5% (media expert) and 90.0% (subject-matter expert), while beta testing among students recorded 92.3%; all results fall within the “Very Feasible” category. These findings indicate that “Sakpole” is technically sound and well received as a game-based cultural learning medium within the Merdeka Curriculum; further experimental research using a pretest-posttest design, and exploration of Augmented Reality integration on the character cards, is recommended.